Acquired haemophilia A in a patient who is a Jehovah's Witness. Issue 8 (29th August 2022) - Brown, Clare; Page, Andrew
Abstract : We detail the case of a man in his 80s who was a Jehovah's Witness, presenting to hospital for the second time in 1 week with atraumatic, severe bruising affecting his right thigh and flank. He was subsequently diagnosed with idiopathic acquired haemophilia A (AHA) and was urgently treated with recombinant factor concentrate and immunosuppressive therapy. Management of his bleeding disorder and resultant severe anaemia was adapted in line with his religious beliefs. AHA is a rare bleeding disorder which should be considered in patients with an isolated prolonged activated partial thromboplastin time and a history of recent or acute bleeding. Prompt diagnosis and management are essential as delays may result in increased mortality. Given that this patient declined blood transfusion, management of his bleeding disorder presented a unique challenge.